Clinical and genetic aspects of Turner’s syndrome - Ibarra Ramírez, Marisol; Martínez de Villarreal, Laura Elia (UANL. Facultad de Medicina, 2016)
Turner’s syndrome, or monosomy X, is defined as the total or partial loss of the second sex chromosome. The clinical phenotype is highly variable and includes short stature, gonadal dysgenesis, pterygium colli, cubitus valgus and low hairline. The variable expressivity of height and other physical features may be only partially related to the chromosomal formula. Currently, the delay in the diagnosis of Turner’s syndrome remains a problem, as only 15---30% of patients are diagnosed during their first year of life. Understanding its complex etiology and learning more about its clinical variability and complications will allow us to advance the therapeutic and management approach of such patients. This review summarizes the clinical characteristics of, and diagnostic tests for, Turner’s syndrome and the advances in the study of its underlying genetic factors